2013
DOI: 10.1002/bmc.2969
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and quantification of 10‐hydroxycamptothecine in Camptotheca acuminate and its medicinal preparation by liquid chromatography–ion trap mass spectrometry

Abstract: A rapid and sensitive method for the identification and quantification of 10-hydroxycamptothecine (HCPT) in Camptotheca acuminata Decne is described. The HCPT standard solution was directly infused into the ion trap mass spectrometers (IT/MS) for collecting the MS(n) spectra. The electrospray ionization (ESI) mass spectral fragmentation pathway of HCPT was proposed and the ESI-MS(n) fragmentation behavior of HCPT was deduced in detail. The major fragment ions of HCPT were confirmed by MS(n) in both negative io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It had identified the active compounds of Chinese herbs in our previous reports [22,23]. Moreover, these reports show that IT mass spectrometers can also be very useful for quantitative analysis.…”
Section: Introductionmentioning
confidence: 92%
“…It had identified the active compounds of Chinese herbs in our previous reports [22,23]. Moreover, these reports show that IT mass spectrometers can also be very useful for quantitative analysis.…”
Section: Introductionmentioning
confidence: 92%
“…The results obtained by LC-FLD were compared with the results reported for LC (Chen et al, 2013b;Zhao et al, 2010;Zu et al, 2004) as estimated by the Student t-test at 95% confidence level, which indicated no significant difference between the LC-FLD method and the reference reported by LC and LC-MS methods. Analysis of real samples was performed on C. acuminata and HCPT injection extracted with methanol under the above conditions.…”
Section: Applicationmentioning
confidence: 85%
“…In order to accurate evaluate and control the quality of C. acuminate and the preparation process of related drugs by CPT and HCPT with low concentrations, it is necessary to establish a reliable and accurate analytical method for the determination of CPT and HCPT (Chen et al, 2013a). In recent years, liquid chromatography (LC) with various detection systems has become the most common approach for the determination of CPT and HCPT in medicinal plants and their medicinal preparations (Chen et al, 2013b;Huang et al, 2005;Lan et al, 2003;Tsaia et al, 2000;Zu et al, 2004). In recent years, liquid chromatography (LC) with various detection systems has become the most common approach for the determination of CPT and HCPT in medicinal plants and their medicinal preparations (Chen et al, 2013b;Huang et al, 2005;Lan et al, 2003;Tsaia et al, 2000;Zu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, high-performance liquid chromatography (HPLC) (Ma et al, 2002), LC-fluorescence or ion trap mass spectrometry (Zheng et al, 2012;Chen et al, 2013b), chemiluminescence (Sun et al, 2011), and LC-ESI-MS/MS (Zhao et al, 2010), were extensively used to detect HCPT. Although widely employed and possessing excellent selectivity and high sensitivity, these methods are high-cost and consume much longer time and labor.…”
Section: Introductionmentioning
confidence: 99%